2006
DOI: 10.1038/sj.ejcn.1602489
|View full text |Cite
|
Sign up to set email alerts
|

Black tea – helpful or harmful? A review of the evidence

Abstract: Objective: To consider whether consumption of black tea has a positive or negative impact on health. Design: Databases were searched for relevant epidemiological and clinical studies published between 1990 and 2004. Results: Clear evidence was found for coronary heart disease (CHD), where an intake of X3 cups per day related to risk reduction. The mechanism could involve the antioxidant action of tea polyphenols. While experimental models have suggested that flavonoids attenuated cancer risk, epidemiological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
154
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(155 citation statements)
references
References 107 publications
0
154
0
1
Order By: Relevance
“…Another relevant flavan-3-ol present in both kinds of samples was EGCG, which showed a much lower concentration in fermented tea. These large concentration differences were expected since flavan-3-ols are oxidised or condensed to other large polyphenolic molecules such as theaflavins and thearubins during the fermentation process (Gardner et al 2007). …”
Section: Differentiation Of Unfermented and Fermented Teamentioning
confidence: 99%
See 1 more Smart Citation
“…Another relevant flavan-3-ol present in both kinds of samples was EGCG, which showed a much lower concentration in fermented tea. These large concentration differences were expected since flavan-3-ols are oxidised or condensed to other large polyphenolic molecules such as theaflavins and thearubins during the fermentation process (Gardner et al 2007). …”
Section: Differentiation Of Unfermented and Fermented Teamentioning
confidence: 99%
“…Intake of tea has been suggested to be associated with a decreased risk of cardiovascular diseases and cancer (Gardner et al 2007;Sharangi 2009). Several phytochemicals, such as polyphenols (phenolic acids, flavan-3-ols, flavonols, and flavones) and alkaloids (theobromine and caffeine) (Figure 1), are found in relatively high amounts in tea.…”
mentioning
confidence: 99%
“…As mentioned above, green tea is probably the most efficient source of antioxidants in our diet (Lin et al 1996;Kris-Etherton et al 2002;Farhoosh et al 2007). However, green tea as well as black tea contains caffeine (Farhoosh et al 2007) and an excessive intake of caffeine can be related to hypertension, dehydration, anxiety, or insomnia (Gardner et al 2007), whereas no adverse effect has been observed on drinking beverages made from leaves of strawberry, blackberry, and raspberry. Therefore, the studied plants may be seen as an attractive alternative source of antioxidants for the group of consumers consciously selecting the intake of higher levels of antioxidants without caffeine.…”
Section: Comparison Of the Antioxidant Capacities Of Herbal Infusionsmentioning
confidence: 99%
“…Theaflavin and thearubigins are polyphenol-class pigment compounds produced during fermentation and play a role in the typical colour of black tea. 8,9 Tea consumption in the world, especially black tea ranks second after water consumption. A study conducted by the UK National Diet and Nutrition Survey (NDNS) with a sample of 7000 adults showed 77% of them drank tea with an average consumption of 2.3 cups (540 ml) of tea per day.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by the UK National Diet and Nutrition Survey (NDNS) with a sample of 7000 adults showed 77% of them drank tea with an average consumption of 2.3 cups (540 ml) of tea per day. 8 The purpose of this study was to determine the effect of black tea on the transverse strength of heat-polymerized acrylic resin.…”
Section: Introductionmentioning
confidence: 99%